Transforming the character of public organizations : Techniques for Change Agents - Rusaw, Carol (Quorum Books, 1998)
From her own experience in various agencies and organizations, Dr. Rusaw knows that to inspire change in any organization and particularly in the public sector, change agents must understand that change is primarily collective, nonrational, and nonlinear. People who seek to create change cannot stand apart from the problems, issues, and concerns raised by their constituents, but must merge themselves into the data-making, analysis, and diagnosis phases of consulting. The agent must, in other words, participate actively in creating change―and how the agent must do this, why, and the effects the agent can expect are the subjects of Dr. Rusaw's book. Few books discuss public sector change in the way Dr. Rusaw does here, and none incorporate the phenomenological perspective that she uses. Her book will appeal to practicing public administrators who seek real-life examples presented in conversational language. It will also be important for teachers and students in public administration, specifically in courses in organizational behavior, leadership, organization theory, human relations, and public personnel management.